(w-6)(w-6)(3)=42

Simple and best practice solution for (w-6)(w-6)(3)=42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (w-6)(w-6)(3)=42 equation:



(w-6)(w-6)(3)=42
We move all terms to the left:
(w-6)(w-6)(3)-(42)=0
We multiply parentheses ..
(+w^2-6w-6w+36)3-42=0
We multiply parentheses
3w^2-18w-18w+108-42=0
We add all the numbers together, and all the variables
3w^2-36w+66=0
a = 3; b = -36; c = +66;
Δ = b2-4ac
Δ = -362-4·3·66
Δ = 504
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$w_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$w_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{504}=\sqrt{36*14}=\sqrt{36}*\sqrt{14}=6\sqrt{14}$
$w_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-36)-6\sqrt{14}}{2*3}=\frac{36-6\sqrt{14}}{6} $
$w_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-36)+6\sqrt{14}}{2*3}=\frac{36+6\sqrt{14}}{6} $

See similar equations:

| 60+1/4x=X | | u+9=18 | | −5x+12=−8x+24 | | (2x+4)2=(7x-13 | | 8(3x+2)–3x=3(5x–4)–2 | | H=-16t+32 | | 12(2.71)^(3x-2)=8 | | –3x+7=10. | | (3x-2)^2-1=48 | | 7.4=v/2.2-0.1 | | 123^(3x-2)=8 | | (3x+6)=(-4x+5) | | 3(j-2)=36 | | 5(2a-3)=13a-3a-5) | | -1(8m-9)=-39 | | -1/2=-1/2b-6/7 | | 8x-11=360 | | 6x+1+8x-11=180 | | -1(8m-9)+12=-27 | | 7u=98u= | | -2.5x-7=-(5+3x) | | (4x+7)=(7x-38) | | x-7.5=18.4 | | 6x+22+64+4x=x | | v+9/4=6 | | 2.5x+5=1/2x+25 | | 18d+3d+5d–21d=15 | | c=2(74)-89 | | -5(x-2)+6(7+3x)=5x+8x | | X^2-14x+18=-19 | | -7(l+3)/2+4=-3 | | 74=2t-89 |

Equations solver categories